Scholar – Fictionist – Memoirist: David Lodge’s Documentary (Self-)Biography in Quite a Good Time to be Born: 1935–1975 - Kusek, Robert (Studia Anglica Posnaniensia, 2016)
Over the last decade or so, David Lodge has become not only a reader but also an avid practitioner of “fact-based writing” - be it the biographical novel (The Master of 2004 and A Man of Parts 2011), the autobiographical novel (Deaf Sentence of 2008), the biographical essay (Lives in Writing of 2014) and - finally - a proper autobiography (Quite a Good Time to Be Born of 2015). The aim of this paper is to analyse Lodge’s recent turn to life narratives and, in particular, his autobiographical story of 2015; and, consequently, to address the following questions: Does Lodge’s memoir offer “an experiment in autobiography” (to quote H.G. Wells, one of Lodge’s favourites), or remain a conventional life story immune to the tenets of contemporary life writing? Is it the work of a (self- )historian, or a novelist? Does it belong to the “regime of truth,” or is it the product of memory? Finally, is it, indeed, a memoir (as its subtitle claims), or a specimen of self-biography? The paper will show special interest in the work’s generic characteristics and will offer an attempt to locate Quite a Good Time to Be Born on the map of contemporary life writing practices.